Y-Box-Binding Protein 1 Interacts with Hepatitis C Virus NS3/4A and Influences the Equilibrium between Viral RNA Replication and Infectious Particle Production - Chatel-Chaix, Laurent (American Society for Microbiology, 2011)

(untitled)
The hepatitis C virus (HCV) NS3/4A protein has several essential roles in the virus life cycle, most probably through dynamic interactions with host factors. To discover cellular cofactors that are co-opted by HCV for its replication, we elucidated the NS3/4A interactome using mass spectrometry and identified Y-box-binding protein 1 (YB-1) as an interacting partner of NS3/4A protein and HCV genomic RNA. Importantly, silencing YB-1 expression decreased viral RNA replication and severely impaired the propagation of the infectious HCV molecular clone JFH-1. Immunofluorescence studies further revealed a drastic HCV-dependent redistribution of YB-1 to the surface of the lipid droplets, an important organelle for HCV assembly. Core and NS3 protein-dependent polyprotein maturation were shown to be required for YB-1 relocalization. Unexpectedly, YB-1 knockdown cells showed the increased production of viral infectious particles while HCV RNA replication was impaired. Our data support that HCV hijacks YB-1-containing ribonucleoparticles and that YB-1–NS3/4A–HCV RNA complexes regulate the equilibrium between HCV RNA replication and viral particle production.